Artificial Intelligence in Sharia Supervision: Legitimacy and Limits of Authority in Indonesia - Muhammad Permadi; Atin Risnawati (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2026)
This research was conducted in response to the increasing imbalance between the number of available Sharia Supervisory Board (DPS) members and the number of LKS, which raises critical concerns regarding the effectiveness of sharia supervision. The purpose of this article is to evaluate the legitimacy and scope of authority, as well as the legal-moral accountability, of Artificial Intelligence within Islamic Financial Institutions (LKS) in Indonesia, particularly in the absence of specific regulations under prevailing laws, Financial Services Authority Regulations (POJK), and DSN-MUI fatwas. Methodologically, this study employs a normative-doctrinal legal research approach with an interdisciplinary framework integrating legislative, conceptual, and Islamic jurisprudence methods. The analysis encompasses the principle of mubāḥ in fiqh muāmalah, the doctrine of maqāṣid al-sharīʼah, and the functional position of AI within sharia governance and supervisory accountability. Findings: This study demonstrates that AI-assisted sharia supervision is legally defensible under Islamic law, provided it operates exclusively as a decision-support system (wasīlah) and that full legal and moral accountability for sharia compliance remains vested in the DPS. Policy Recommendations: This study urges the OJK to issue explicit regulatory instruments governing prudential standards, algorithm governance, and legal accountability in AI-assisted sharia supervision, and calls upon the DSN-MUI to issue a dedicated fatwa establishing the ethical framework and normative boundaries for AI application in DPS supervisory functions.